Validation of a growth estimation method: Application to the flathead mullet, Mugil cephalus in the Northern coast of Senegal - Ndour, Ismalla (JOURNAL OF ADVANCES IN BIOLOGY, 2016)
Growth parameters estimation (Linf and K) of Mugil cephalus in the Northern coast of Senegal was made with the ELEFAN in R program, based on biological sampling carried out on three landing sites (Kayar, Fass Boye, Saint-Louis) inthe Northern coast of Senegal at sea and on the Senegal River in 2011. The results obtained were 58.8 cm FL for asymptotic length and 0.32 years-1 for the growth coefficient of the Von Bertalanffy equation. The total mortality (Z) of juveniles was higher than that of adults of the species. Linf and K values were closed to those estimated in the literature, confirming the relevance of the use of the 'ELEFAN in R' Model in the estimation of growth parameters of the Von Bertalanffy equation.